2006
DOI: 10.1007/s11664-006-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si Co Doping on Ferromagnetic Properties of GaGdN

Abstract: Single-phase GaGdN and GaGdN:Si films were grown on sapphire substrates by gas source molecular beam epitaxy using solid Gd, Ga, and Si sources and active nitrogen derived from a RF nitrogen plasma source. The undoped films were highly resistive films but became conductive with the addition of Si. Superconducting quantum interference device magnetometry indicated roomtemperature ferromagnetism in both types of materials. Structural defects had a strong influence on the magnetic ordering of the material, as see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…[8][9][10][12][13][14] Only few exceptions show partly ferromagnetic samples or no ferromagnetism. 15,16 The origin of the ferromagnetic order in GaN:Gd is still unknown. It was shown that cation vacancies can provide local moments which exchange directly by their overlapping wave functions and provide a long-ranged coupling mechanism.…”
mentioning
confidence: 99%
“…[8][9][10][12][13][14] Only few exceptions show partly ferromagnetic samples or no ferromagnetism. 15,16 The origin of the ferromagnetic order in GaN:Gd is still unknown. It was shown that cation vacancies can provide local moments which exchange directly by their overlapping wave functions and provide a long-ranged coupling mechanism.…”
mentioning
confidence: 99%
“…The substrate and the kind of MBE seem to be of minor importance. For 6 H ‐SiC , sapphire , and LiAlO 2 as substrates and plasma‐assisted as well as reactive MBE hysteretic magnetization behavior at room temperature has been observed. Ferromagnetic behavior was reported for Gd concentrations in the few percent range as well as for the lower doping level concentration range down to 10 16 cm −3 .…”
Section: Growth Methods Influence On the Magnetic Properties Gd‐doped Ganmentioning
confidence: 88%
“…Teraguchi et al reported room temperature ferromagnetism in molecular beam epitaxy (MBE) grown Ga 0.94 Gd 0.06 N in 2002. Later, ferromagnetism in GaN:Gd was demonstrated by several groups . Ferromagnetism was observed for samples where the Gd was incorporated during MBE growth as well as in samples where the Gd was implanted .…”
Section: Introductionmentioning
confidence: 95%
“…Pearton et al reported the room temperature FM for the Gd-implaned GaN [16]. They also observed the increase of magnetization with the increase of co-doped Si concentration [17]. On the other hand, Dhar et al reported the colossal magnetic moment in the low Gd concentration (10 16 -10 18 cm -3 ) of GaGdN grown by MBE and explained within the framework of the phenomenological model [18].…”
Section: Introductionmentioning
confidence: 99%